Intracardiac impedance after cardiac resynchronization therapy is a novel predictor for worsening of heart failure - Suzuki, Hitoshi; Nodera, Minoru; Kamioka, Masashi; Kaneshiro, Takashi; Kamiyama, Yoshiyuki; Takeishi, Yasuchika (Heart and vessels, 2017)
Intrathoracic impedance measured by cardiac resynchronization therapy (CRT) varies because several factors other than pulmonary congestion may affect this parameter. Therefore, we hypothesized that changes in intracardiac impedance between the right and left ventricular leads would be more accurate to identify worsening heart failure in patients with CRT. The study enrolled 21 patients with CRT defibrillator (15 males, 70 ± 12 years). During the follow-up period (12 ± 7 months), the subjects experienced 37 fluid index threshold (60 ohm-days) crossing events. These events were divided into two groups whether hospitalization due to worsening heart failure was required (group-H, n = 14) or not (group-NH, n = 23). Based on the intracardiac impedance at the beginning of increasing fluid index (BI) and the crossing of 60 ohm-days (CI), the rate of impedance change (BI–CI/BI) was estimated. Then, the time elapsed from BI to CI ( T ) was evaluated. We calculated the rate of intracardiac impedance change per day (BI–CI/BI × T ) in each group. The rate of intrathoracic impedance change per day was also determined using the same method. The median rate of intracardiac impedance change per day was 0.27 (IQR 0.22–0.54) %/day in group-H, and 0 (IQR 0–0.08) %/day in group-NH with a significant difference ( P < 0.0001), whereas the rate of intrathoracic impedance change per day was similar between the two groups. By receiver operating characteristic curve for identification of hospitalization due to worsening heart failure, the best cutoff value of the rate of intracardiac impedance change per day was 0.20%/day (sensitivity 92%, specificity 88%, and AUC 0.98). In contrast, the best cutoff value of the rate of intrathoracic impedance change per day was 0.19%/day (sensitivity 86%, specificity 43%, and AUC 0.68). These results suggest that increased rate of change of decreasing intracardiac impedance measured by CRT is a novel useful predictor for worsening heart failure.